2006
DOI: 10.1249/01.mss.0000183860.42853.15
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Conjugated Linoleic Acid Supplementation during Resistance Training

Abstract: Supplementation with CLA during resistance training results in relatively small changes in body composition accompanied by a lessening of the catabolic effect of training on muscle protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
62
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 35 publications
(81 reference statements)
4
62
0
1
Order By: Relevance
“…Kreider et al (18) and Pinkoski et al (21), who investigated the effects of CLA supplementation during resistance exercise training on subjects performing different sporting activities, observed different results despite the fact that both performed randomized controlled studies. Conjugated linoleic acid supplementation in experienced resistance-trained athletes did not induce differences in total body mass, body composition, and strength (18), whereas in moderately physically active subjects, CLA induced a relatively small increase in lean body mass and a decrease in body fat mass (21).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Kreider et al (18) and Pinkoski et al (21), who investigated the effects of CLA supplementation during resistance exercise training on subjects performing different sporting activities, observed different results despite the fact that both performed randomized controlled studies. Conjugated linoleic acid supplementation in experienced resistance-trained athletes did not induce differences in total body mass, body composition, and strength (18), whereas in moderately physically active subjects, CLA induced a relatively small increase in lean body mass and a decrease in body fat mass (21).…”
Section: Introductionmentioning
confidence: 77%
“…The subjects ingested 7 opaque soft gel capsules of CLA (6 g of Tonalin FFA 80; Cognis Group, Monheim, Germany) or PLA (6 g of sunflower oil) per day, both identical in taste and in appearance. The CLA and placebo dosages were used in literature in studies that investigated the effect of CLA supplementation on body mass composition (18,21); moreover, this CLA dose is suggested by the food supplement manufacturers. The CLA supplement was a mixture containing 40% c9,t11-CLA and 40% t10,c12-CLA.…”
mentioning
confidence: 99%
“…Considering this fact, the above result brings up the question of the validity of using ultrasonic muscle thickness determined at rest to evaluate individual differences in muscle size. In previous studies, muscle thickness measurements with ultrasonography have been performed in standing (Abe et al, 1994;Akagi et al, 2010;Kubo et al, 2003aKubo et al, , 2003bMiyatani et al, 2003Miyatani et al, , 2004Pinkoski et al, 2006;Toji and Kaneko, 2007;Wakahara et al, 2010), supine (Ainscough-Potts et al, 2006;Arts et al, 2010;Campbell et al, 1995;Pillen et al, 2003Pillen et al, , 2007Reimers et al, 1998;Scholten et al, 2003), or prone (Candow and Chilibeck, 2005;Candow et al, 2006;Mohagheghi et al, 2007;Reimers et al, 1998) positions. In the standing position, the gravitational force acted on the muscles of interest in the proximal-distal direction.…”
Section: Discussionmentioning
confidence: 99%
“…Although CLA supplementation in the study dose apparently does not pose a health risk 19 , the participants' reports raise concern about CLA supplementation. Other studies 9,23 have already reported CLA-related side effects, generally related to the gastrointestinal tract. The most frequently reported side effects were indigestion, heartburn, reflux, flatulence, nausea, diarrhea, bloating, constipation, loss of appetite, and itchy face 9,23 .…”
Section: Discussionmentioning
confidence: 97%
“…These differences greatly hinder study comparison. In addition, CLA action seems to differ between overweight 17,18 and normal weight individuals [23][24][25] . Therefore, it is important to point out that the study sample consisted exclusively of overweight/ obese women, and excess weight is a multifactorial phenomenon characterized by significant metabolic and/or behavioral changes, which consequently, are hard to control 26 .…”
Section: Discussionmentioning
confidence: 99%